Association of Practice of Sports in and out-of-school with Scholar Performance - Evidence from Moscow and Saint Petersburg: a Longitudinal Study - Edgar Demetrio Tovar-García (Brazilian Army, 2017)
Introduction: It is well known the maxim mens sana in corpore sano (a sound mind in a healthy body), which suggests a positive nexus between sports and educational outcomes. However, this nexus has been empirically studied mostly in the USA, where the results are mixed, even suggesting that participation in sports may negatively influence educational outcomes. Objective: This article empirically studies the relationship between sport activities at school and out-of-school and educational achievements of school students from 1st to 11th grade in Moscow and Saint Petersburg, Russia. Methods: This was a longitudinal observational study, that used data from the Russia Longitudinal Monitoring Survey, annual observations covering the period 2010-2015 and 1529 observations were examined. Associations were examined using ordered probit regressions with panel data. Results: Sport activities at school do not have statistically significant links with school grades. Conversely, sport activities out-of-school are positively associated with educational achievements. Specifically, in the case of boys, participation in ball sports increases their probabilities of having obtained higher school grades. For girls, participation in other sports out-or-hours school increases those probabilities. However, spending more than  10 hours on sports reduces those likelihoods. Conclusion: Parents and teachers should encourage the participation of their children in sport activities; this will benefit their educational outcomes. However, the practice of sports at school is irrelevant, indicating that policy makers should restore the quality of physical education classes.   Associação de prática de esportes dentro e fora da escola com desempenho escolar - evidências de Moscou e São Petersburgo: um estudo longitudinalIntrodução: O lema mens sana in corpore sano (mente saudável no corpo saudável) é amplamente conhecido e sugere uma conexão positiva entre os resultados do esporte e a educação. Tal conexão tem sido testada empiricamente, principalmente nos Estados Unidos, mas os resultados são controversos, sendo que alguns estudos sugerem que a participação no esporte poderia ter influências negativas nos resultados educativos. Objetivo: Examinar a relação das atividades esportivas, na escola e fora desta com os resultados escolares de estudantes do 1º ao 11º ano na Escola Primaria em Moscou e Sam Petersburgo, Rússia. Métodos: Estudo de observação longitudinal que utilizou dados do Rússia Longitudinal Monitoring Survey (RLMS), com observações anuais que cobriram o período de 2010-2015. Participaram do estudo 571 crianças em idade escolar e 1529 observações compuseram as análises. As correlações foram examinadas usando regressões Probit com panéis de dados. Resultados: As atividades esportivas na escola não apresentaram correlação com os resultados das notas escolares (p>0,05). Por outro lado, as atividades esportivas fora da escola mostraram benefício positivo no desempenho educacional. Especificamente, no caso dos meninos, a participação nos esportes de bola aumentou a probabilidade de se obterem notas maiores na escola. Para as meninas, a participação em esportes fora da escola também favoreceu o desempenho escolar. Porem, tanto para meninas quanto para meninos, dedicar mais de 10 horas por semana aos esportes prejudica o desempenho escolar. Conclusão: Pais e professores devem estimular a participação das crianças em atividades esportivas pois apresentam benefícios para os resultados educacionais. Porem, a prática dos esportes na escola mostrou-se irrelevante nos resultados, escolares indicando que as políticas educacionais deveriam acrescentar e exigir maior qualidade das atividades físicas na escola (educação física escolar).